[In the dark ; PNOC ; Komiks relief [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Looks into the four-long hour daily power interruptions in the city ; the causes and prospects for improvement of the electric power and the Geothermal energy source in Mt. Apo in Mindanao run by PNOC ; and a fresh look at Filipino komiks as the number one reading source of Filipino readers.